Kontrol Sosial dalam Menghadapi Praktek Pungli di Area Perkebunan Teh Sidamanik: Studi Kasus: Sidamanik Sumatera Utara - Bonita Silalahi; Marisa Elsera; Siti Arieta (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
As tourism progresses in Indonesia, it is still inseparable from illegal levies, one of which is the tourism of the Sidamanik tea garden, initially used as a tourist object to fulfill the people's economy, it has turned into tourism which has problems, namely extortion by teenagers. Weak supervision from parents is one of the causes of deviant behavior supported by the lack of attention from educational institutions and guidance from police agencies in the Siamanik tourism environment. This research uses descriptive qualitative which conducts research by determining informants based on purposive sampling proposed by Creswell. The results of this study are bringing Sidamanik tourism which is an image of the area, where there is extortion behavior carried out by organizations formed by teenagers starting from the free sex behavior of visiting tourists strengthened by weak social control from parents, educational institutions, educational institutions police.